(untitled) (Research, Society and Development, 2021)
The Input-Product Matrix is ​​a tool used to perform analysis of the productive sectors and their interrelations, helping to make economic decisions, and contributing to a better planning of the key sectors for the development of a region. In this way, this work sought to implement a multisectoral analysis of Rondônia’s economy based on the Input-Output Matrix for the 2018 economic structure. Data from Brazil and the twenty-seven units of the federation were analyzed. The sectors that stood out in the state economy were found to be Information and communication, Manufacturing, and Accommodation and food in intra-regional relations, and the sectors of Transport, storage and mail, Construction, and Extractive industries for interregional relations. The findings make it possible to contribute to the development of policies that stimulate the highlighted sectors, supported by the growth of production and in line with the most relevant proposals for sustainable development in the Amazon.